2012
DOI: 10.1007/s10875-012-9700-5
|View full text |Cite
|
Sign up to set email alerts
|

Dual Analysis for Mycobacteria and Propionibacteria in Sarcoidosis BAL

Abstract: Purpose Sarcoidosis is a non-caseating granulomatous disease for which a role for infectious antigens continues to strengthen. Recent studies have reported molecular evidence of mycobacteria or propionibacteria. We assessed for immune responses against mycobacterial and propionibacterial antigens in sarcoidosis bronchoalveolar lavage (BAL) using flow cytometry, and localized signals consistent with microbial antigens with sarcoidosis specimens, using matrix-assisted laser desorption ionization imaging mass spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 36 publications
0
69
0
6
Order By: Relevance
“…The lung is a unique environment with constant exposure to foreign antigens. Mycobacterial antigens or signals consistent with mycobacterial antigens have been localized to sarcoidosis granulomas (34,35) The distinction in local versus peripheral PD-1 expression could reflects distinction in microbial antigen load, which has been shown to affect immune function and drive PD-1 up-regulation (36). Thus, the observation of high spontaneous cytokine production and increased PD-1 expression likely reflects the consequences of the host immune system attempting to clear persistent, foreign antigen while minimizing organ destruction.…”
Section: Discussionmentioning
confidence: 99%
“…The lung is a unique environment with constant exposure to foreign antigens. Mycobacterial antigens or signals consistent with mycobacterial antigens have been localized to sarcoidosis granulomas (34,35) The distinction in local versus peripheral PD-1 expression could reflects distinction in microbial antigen load, which has been shown to affect immune function and drive PD-1 up-regulation (36). Thus, the observation of high spontaneous cytokine production and increased PD-1 expression likely reflects the consequences of the host immune system attempting to clear persistent, foreign antigen while minimizing organ destruction.…”
Section: Discussionmentioning
confidence: 99%
“…The same author in his subsequent paper reported that ESAT-6 induces the most frequent stimulation of Th1 immune response in these patients, as compared to katG, Ag85A, sodA and Hsp70 [19]. Recently, Oswald-Richter et al, using matrix-assisted laser desorption ionization imaging mass spectrometry localized signal consistent with antigen ESAT-6 in sarcoidosis granulomas [20].…”
Section: Oswald-richter Et Al Detected Cd4mentioning
confidence: 93%
“…Dubaniewicz and colleagues identified mycobacterial heat shock proteins in lymph nodes from patients with sarcoidosis using immunohistochemistry [94]. Using a directed candidate approach, Drake and colleagues screened sarcoidosis tissue samples by mass spectrometry and detected a mass-tocharge (m/z) signal compatible with the mycobacterial protein, ESAT6 [95].…”
Section: Role Of Mycobacterial Organisms In Sarcoidosismentioning
confidence: 99%